Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/bjh.15881
|View full text |Cite
|
Sign up to set email alerts
|

G‐CSF administration prior to donor lymphocyte apheresis promotes anti‐leukaemic effects in allogeneic HCT patients

Abstract: Summary Donor lymphocyte infusion (DLI) is an effective method to establish full donor chimerism or to prevent and treat relapse after allogeneic haematopoietic cell transplantation (allo‐HCT). Usually, DLIs are collected from naïve donors as steady‐state lymphocytes. When donor lymphocytes are collected during stem cell apheresis, donors are pre‐treated with granulocyte colony‐stimulating factor (G‐CSF). However, the impact of G‐CSF stimulation and the resulting composition of DLIs on beneficial anti‐leukaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In vitro studies showed less antitumoral activity for T cells harvested after G-CSF stimulation [ 15 ], in contrast to the literature reports that have tended to document better outcomes with gDLI [ 27 ]. Abbi’s study compared the outcome of classical DLI and gDLI in 67 patients (including 70% of myeloid malignancies), 15 of whom with gDLI and 52 with classical DLI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies showed less antitumoral activity for T cells harvested after G-CSF stimulation [ 15 ], in contrast to the literature reports that have tended to document better outcomes with gDLI [ 27 ]. Abbi’s study compared the outcome of classical DLI and gDLI in 67 patients (including 70% of myeloid malignancies), 15 of whom with gDLI and 52 with classical DLI.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS was 10.4 months [ 10 ]. More recently, Schneidawind reported a study of 44 patients mostly treated for AML and MDS, with curative, pre-emptive or prophylactic indication; patients treated with gDLI had a better outcome compared to patients treated with classical DLI in terms of chimerism conversion (75% vs. 25%, p = 0.006), 1 year cumulative incidence of relapse (46% vs. 70%, p = 0.04) and 1-year OS (46% vs. 70%, p = 0.04), without excess of GVHD [ 27 ]. The differences between our results and the latter publication may be explained by treatment associated with DLI or outcomes in the prophylactic situation.…”
Section: Discussionmentioning
confidence: 99%
“…The DLIs derived from PBSCs collected after G-CSF treatment favored the conversion to full donor chimerism, despite the higher content of M-MDSCs. Moreover, G-CSF-treated DLIs were associated with lower cumulative incidences of relapse and disease progression, and did not significantly increase the cumulative incidence of GVHD (63). Additionally, during the first 100 days after allo-HSCT, the number of MDSCs in peripheral blood was correlated with the occurrence of severe acute GVHD, but not with an increased risk of malignancy recurrence (64).…”
Section: Impact Of Mdscs On the Gvt Effectmentioning
confidence: 98%
“…We reported previously that G-CSF administration prior to donor lymphocyte apheresis results in an improved conversion to complete donor chimerism and a lower incidence of relapse or progression without increasing the risk of GVHD after infusion of donor lymphocytes. We also identified higher numbers of hematopoietic stem and progenitor cells, myeloid-derived suppressor cells and monocytes as independent risk factors for an improved overall survival (42). In the present study, 26 DLIs were derived from donors that were pretreated with G-CSF.…”
Section: Discussionmentioning
confidence: 93%